2017
DOI: 10.21470/1678-9741-2017-0056
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dyssynchrony and Ventricular Function in Right Univentricular Stimulation at Different Positions

Abstract: IntroductionChronic stimulation of the right ventricle with pacemaker is associated with ventricular dyssynchrony and loss of contractility, even in subjects without previous dysfunction. In these patients, there is a debate of which pacing site is less associated with loss of ventricular function.ObjectiveTo compare pacemaker-induced dyssynchrony among different pacing sites in right ventricular stimulation.MethodsCross-sectional study of outpatients with right ventricle stimulation higher than 80% and preser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(20 reference statements)
0
3
0
2
Order By: Relevance
“…The effects of right ventricular septal pacing in terms of maintaining ventricular synchrony and cardiac function are still controversial. [13][14][15][16][17][18] With the rapid development of technology, many studies have confirmed the advantage of left bundle branch area pacing. Studies proved that left bundle branch area pacing produces narrower-paced QRS duration and better echocardiographic cardiac function than does right ventricular septal pacing.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of right ventricular septal pacing in terms of maintaining ventricular synchrony and cardiac function are still controversial. [13][14][15][16][17][18] With the rapid development of technology, many studies have confirmed the advantage of left bundle branch area pacing. Studies proved that left bundle branch area pacing produces narrower-paced QRS duration and better echocardiographic cardiac function than does right ventricular septal pacing.…”
Section: Discussionmentioning
confidence: 99%
“…Основными местами позиционирования электродов являются апикальная и септальная позиции, при этом часть исследователей [10,11] отдают предпочтение апикальному расположению. По данным C. Gerald et al [12], размещение электрода в септальной позиции имеет эффективность, схожую с эффективностью при апикальном размещении.…”
Section: выбор икд и позиционирования электродовunclassified
“…The degree of electrical dyssynchrony induced by right ventricular pacing can be calculated by the duration of the paced QRS. However, Osório, et al found that QRS complex duration did not correlate well with pacing position and correlated poorly with dyssynchrony parameters . The use of variable echocardiographic modalities to assess the ventricular dyssynchrony is very important especially using tissue Doppler imaging (TDI) and 2D speckle tracking echocardiography .…”
Section: Introductionmentioning
confidence: 98%